Request of the Spanish Government for the technical assistance of the League in the study of measures for providing food supplies for refugees (report) - Bray, Denys, 1875-1951
1938-11-03 032-0199-007 - 6 - probably need from the outset three deputies (one preferably a medical man) at Barcelona, Madrid and Valencia, a small central office, and a staff of about eight Spanish-speaking inspectors equipped with light vans. To ensure efficiency of distribution, some augmentation of existing motor transport facilities would be essential. 14. In this problem there is no room for counsels of perfection, and it is imperative that the refugee ration should bear some real relationship to what a member of the civil population secures under his Government's ration supplemented by what he can get by hook or by crook otherwise. The ration proposed by the Spanish Government, after preliminary discussion with ourselves, seems to us to represent a bare but fair minimum,framed to accord as far as possible with the customary diet of the country. It is admittedly a minimum, but it is more than what the refugee is getting now. On the other hand, whereas he has been able during the summer to eke out his ration in devious ways on the countryside, such pickings will disappear with the onset of winter. 15. We have been confronted again and again with the fact that even now refugees are getting more with the poorest strata of the non-working civil population, who are supported by public assistance. This disparity is probably accentuated in Madrid (which we were not able to visit) owing to the existence, of refugees from within, side by side with natives of Madrid, who, after being evacuated and becoming refugees elsewhere, have despite all Government discouragement managed to crowd back, and are technically refugees no longer. The annexed note by the Spanish Government contains an assurance that, given a refugee relief scheme, this disparity would be reduced as far as possible. 16. We are oppressed by the urgency as well as the magnitude of the problem. Even under the most favourable conditions it would take a considerable time to get any relief scheme into full swing, and the present private organisations, admirable as their work has been, cannot do more than touch the fringe of the problem. We hope that they will receive increasing support, but we urge that, if a comprehensive scheme such as we suggest proves acceptable, no time should be lost in obtaining appropriate help from Governments and especially from nations with surplus stocks of wheat, dried fish, skimmed milk, cocoa and other essential supplies. 17. The Spanish Government's financial proposals are contained in their memorandum attached. 18. We greatly appreciated the courtesy of the Spanish Government which afforded us every facility in the course of our investigations. From Mr. de Lilliehook, the Commissioner of the International Commission for the Assistance of Child Refugees in Spain, Mr. Jacob, Dr. Audrey Russell and other members of the Society of Friends, and Mr. Olgiati of the Swiss Relief Committee, we received the invaluable assistance of their first-hand experience of relief work in Spain. We have the honour to be, Sir, Your obedient Servants, (Signed) DENYS BRAY L. WEBSTER 292/946/32/199(vi)